Bank Indonesia's Role in Developing the Creative Economy In Gorontalo Province - Latif, Abdul; Ardi, Muhammad (Jeksyah: Islamic Economics Journal, 2022)
The creative economy is a formula for developing an economy that favors the people, not social engineering to oppress and kill the people's economy. Indonesia is very rich in the creative economy because the creative economy is a new economic sector that is considered by every perpetrator, not only as a job seeker but able to create jobs. The cultural heritage of each region in Indonesia is a capital to compete in the creative industry. This research aims to find out the role of Bank Indonesia in developing the Creative Economy in Gorontalo Province. This research is a type of qualitative research with descriptive methods. The data collection techniques used in this research are observation, interviews, and documentation. From the results of the research, the author found that the role of Bank Indonesia in developing the creative economy, in this case, is the karawo business in Gorontalo Province, which is carried out by providing training, direction, guidance, and assistance to craftsmen, of course, to improve the quality and quantity of a product, so that it can always meet market demand, and of course, it has a good impact on the income and sales of creative industry players, especially karawo craftsmen. fostered by Bank Indonesia. The activities carried out by Bank Indonesia, further spurs the creativity of creative economy actors, especially karawo embroidery, increasing pride in karawo and providing a high economic empowerment impact for craftsmen, entrepreneurs, designers, tailors, and supporting businesses such as culinary, salons, and other businesses.